Correlation of the National Emergency Medicine M4 Clerkship Examination with USMLE Examination Performance - Lawson, Luan E.; Musick, Davis; Brewer, Kori L. (My University, 2015)
Assessment of medical students’ knowledge in clinical settings is complex yet essential to the learning process. Clinical clerkships use various types of written examinations to objectively test medical knowledge within a given discipline. Within emergency medicine (EM), a new national standardized exam was developed to test medical knowledge in this specialty. Evaluation of the psychometric properties of a new examination is an important issue to address during test development and use. Studies have shown that student performance on selected standardized exams will reveal students’ strengths and/or weaknesses, so that effective remedial efforts can be implemented. Our study sought to address these issues by examining the association of scores on the new EM national exam with other standardized exam scores.